A Labor Market Equilibrium Model of the Personal Distribution of Earnings - Creedy, John; Lye, J. N.; Martin, V. L. (Journal of Income Distribution®, 1997)
A model of the distribution of income is derived from a two market general equilibrium model consisting of a goods market and a labor market. The dynamics of income distributional changes as well as their stationary counterparts are also derived.